PENGARUH MODEL PEMBELAJARAN BERBASIS MASALAH TERHADAP PENGETAHUAN DAN SIKAP IBU TENTANG POLA ASUH PADA BAYI - A.Achmad Fariji; Retno Dumilah (Poltekkes Kemenkes Bandung, 2021)
Lack of knowledge of mothers about parenting in children that is practiced in feeding, health care, providing stimulation and emotional support needed by children. To increase the knowledge and attitudes of mothers about good parenting to their children, one of the most effective learning models is the problem-based learning model. The Objective of this study is to determine the effect of problem-based learning models on the knowledge and attitudes of pregnant women about infant care in the working area of ​​the Rengasdengklok Health Center, Kab. Karawang. The research method used is quasi-experimental, the data source used is primary data. The sample was some pregnant women who were selected according to the inclusion criteria, the number of samples was 31 respondents for each group. The analytical test used is the dependent T test. The results of the analysis showed that there were significant average differences in all groups, both in knowledge and attitudes, but the intervention group had a greater difference in average knowledge than the non-intervention group. In attitudes, it is known that there is a significant average difference in all groups, but the intervention group has a greater average difference in attitude (7.7) compared to the non-intervention group. Conclution of this study is an increase in the average value of knowledge and attitudes in the pretest and posttest measurements in both the intervention group and the non-intervention group.Keywords: knowledge, attitude, problem based learning.